Analysis of LAN Network Quality at PTPN7 Senabing Unit in Lahat Regency Using Qos (Quality Of Service) - Amanda Rahma Dwi; Dedi Haryanto; Apriansyah (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
In the era of globalization, human dependence on telecommunications continues to grow, particularly in communication technology. Modern technology has become essential for enabling fast interaction and efficient information exchange. Internet networks not only provide rapid access to information but also allow users to share and obtain data from various global sources. South Sumatra has experienced significant expansion in internet infrastructure, with more than 4,000 BTS (Base Transceiver Stations) installed to support stable communication, including in Lahat Regency. The region currently offers 2G, 3G, and 4G services from providers such as Telkomsel and Indosat. However, internet performance is often disrupted by unexpected power outages and uneven infrastructure in remote areas, resulting in unstable connectivity. This study aims to evaluate network quality at PTPN 7 Senabing Unit, Lahat Regency, using Quality of Service (QoS) parameters including throughput, delay, packet loss, and jitter. Measurements were conducted using Wireshark to monitor and capture data packet traffic. Results indicate variations in delay between daytime and nighttime transmissions. During daytime hours, the delay value reached 6.4 ms, falling into the “Very Good” category.